Exploring EFL Students' Experiences In Using AI Tools to Support Academic Writing - Munawaroh, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This qualitative study investigates how English as a Foreign Language (EFL) students at Institut Agama Islam Nahdlatul Ulama (IAINU) Bangil experience and utilize artificial intelligence (AI) tools in their academic writing processes. Through a phenomenological approach, we conducted in-depth interviews, focus group discussions, and collected written reflections from 25 English education students over four months. Our thematic analysis uncovered four primary themes that characterize their experiences: enhanced writing efficiency and productivity, valuable language learning support and scaffolding, significant challenges to critical thinking and originality, and complex ethical considerations surrounding academic integrity. While participants reported substantial improvements in writing fluency and reduced anxiety when using AI tools like ChatGPT, Grammarly, and QuillBot, they simultaneously expressed concerns about potential over-dependence and the authenticity of their work. These findings illuminate the reality of AI integration in EFL writing contexts and highlight the urgent need for comprehensive institutional policies and pedagogical frameworks that can maximize benefits while addressing legitimate concerns about independent learning and academic honesty.